Spanish-Language Measures of Mania and Depression - Ruggero, Camilo J. (2004)
Efforts to better understand bipolar spectrum disorders across ethnic groups are often hampered by the lack of commonly used self-report instruments to assess mania and depression in individuals who speak languages other than English. This article describes the translation into Spanish of 2 self-report measures of manic symptoms (i.e., the Internal State Scale and the Hypomanic Personality Scale) and 2 self-report measures of depression (i.e., the Inventory to Diagnose Depression and the Inventory to Diagnose Depression, Lifetime version). The authors translated these measures into Spanish and assessed their psychometric properties among bilingual college students (N = 88). Results suggest that the Spanish versions have psychometric properties comparable to the English versions of the instruments.